2021
DOI: 10.1017/s1368980021001671
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the limits of sex: a systematic review concerning food and nutrition in transgender populations

Abstract: Objective To examine the literature and identify main themes, methods, and results of studies concerning food and nutrition addressed in research on transgender populations. Design A systematic review conducted through July 2020 in the MEDLINE/PubMed, Scopus, and Web of Science databases. Results Of the 778 studies identified in the databases, we selected 37. The studies were recent, most of them published after 2015, being produced in Global North countries. The most o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Further, even when their needs are covered by public health systems, barriers of access, stigma, and discrimination can prevent transgender people from accessing covered services, necessitating payments to private providers for required services [ 31 , 32 ]. As with all personal costs, direct health costs are associated with food insecurity [ 33 ], so the need to perform gender affirming procedures can increase this insecurity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, even when their needs are covered by public health systems, barriers of access, stigma, and discrimination can prevent transgender people from accessing covered services, necessitating payments to private providers for required services [ 31 , 32 ]. As with all personal costs, direct health costs are associated with food insecurity [ 33 ], so the need to perform gender affirming procedures can increase this insecurity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported a number of health behavior changes that resulted from stay-at-home conditions during the first year of the pandemic, including altering their diet and exercise. Much of the current literature on nutrition and eating behaviors among transgender populations has followed the biomedical disease model, focusing largely on eating disorders in lieu of broader explorations of nutrition and exercise among trans individuals ( Gomes et al, 2021 ). Current nutritional guidelines rely on a narrow gender binary for making recommendations for daily nutrition, leaving trans and nonbinary individuals without adequate health and nutrient information, nor a sufficient body of literature to build culturally tailored recommendations upon ( Gomes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the current literature on nutrition and eating behaviors among transgender populations has followed the biomedical disease model, focusing largely on eating disorders in lieu of broader explorations of nutrition and exercise among trans individuals ( Gomes et al, 2021 ). Current nutritional guidelines rely on a narrow gender binary for making recommendations for daily nutrition, leaving trans and nonbinary individuals without adequate health and nutrient information, nor a sufficient body of literature to build culturally tailored recommendations upon ( Gomes et al, 2021 ). In our study, participants reported that stay-at-home working conditions and additional time spent in the home allotted for more time to prepare food, more intentional control over their diet, and greater time spent exercising; behaviors that could improve physical health and well-being.…”
Section: Discussionmentioning
confidence: 99%